2011
DOI: 10.1111/j.1365-2966.2011.19566.x
|View full text |Cite
|
Sign up to set email alerts
|

Low-frequency oscillations in black holes: a spectral-timing approach to the case of GX 339-4

Abstract: We analysed Rossi X‐ray Timing Explorer (RXTE)/PCA and HEXTE data of the transient black hole binary GX 339‐4, collected over a time‐span of 8 years. We studied the properties and the behaviour of low‐frequency quasi‐periodic oscillations (QPOs) as a function of the integrated broad‐band variability and the spectral parameters during four outbursts (2002, 2004, 2007 and 2010). Most of the QPOs could be classified following the ABC classification which has been proposed before. Our results show that the ABC cla… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

52
273
4

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 203 publications
(329 citation statements)
references
References 47 publications
52
273
4
Order By: Relevance
“…After that, the spectral parameters were compatible with the source changing from the LHS to the HIMS (until MJD ∼ 55303.6), then to softer states (to the SIMS until MJD 55304.7, then quickly to the SS, MJD ∼ 55306.1, and finally back to the SIMS and HIMS (see Fig. 3) around MJD 55320 (Motta et al 2010b), but this is beyond the scope of our paper because it happened after the observations listed in our Tables.…”
Section: X-ray and γ-Ray Spectramentioning
confidence: 81%
“…After that, the spectral parameters were compatible with the source changing from the LHS to the HIMS (until MJD ∼ 55303.6), then to softer states (to the SIMS until MJD 55304.7, then quickly to the SS, MJD ∼ 55306.1, and finally back to the SIMS and HIMS (see Fig. 3) around MJD 55320 (Motta et al 2010b), but this is beyond the scope of our paper because it happened after the observations listed in our Tables.…”
Section: X-ray and γ-Ray Spectramentioning
confidence: 81%
“…We find that the QPO frequency becomes ≈30% lower in accordance with the ≈20% decrease of the hard X-ray luminosity in the 15-50 keV band. LF QPOs (below 10 Hz) were detected in many BHXBs during the low/hard and intermediate states, such as XTE J150−564 (e.g., Cui et al 1999;Sobczak et al 1999) and GX 339−4 (e.g., Miyamoto et al 1991;Motta et al 2011;Tamura et al 2012). Previous studies suggested that their frequencies are positively correlated with the photon index of the Comptonization below ≈10 Hz, at which the correlation saturates (Vignarca et al 2003;Titarchuk & Fiorito 2004;Titarchuk & Shaposhnikov 2005).…”
Section: Origin Of Qpomentioning
confidence: 99%
“…The state is defined by changes in the PDS. The identifying feature is the presence of the so-called type-B QPO, which has been shown not to be an evolution of the one observed in the HIMS (type-C QPO; see Belloni et al 2005;Casella et al 2004Casella et al , 2005Motta et al 2011Motta et al , 2012. Notice that the SIMS in the HRD is characterised by a drop in total fractional rms (the ellipse in Fig.…”
Section: Soft Intermediate Statementioning
confidence: 99%
“…With the presence of a geometrically thick ADAF in the inner part of the flow, the PRCB can again operate efficiently in creating the magnetic field necessary for the production of a jet. The SIMS is entered again, as indicated by the appearance of type-B QPOs (Stiele et al 2011;Motta et al 2011).…”
Section: Soft Intermediate State At Low Luminositymentioning
confidence: 99%